(untitled) (ModaPalavra e-periódico, 2010)
This article seeks to historicize the male beauty through the ages, from masculinity in ancient Egypt until today’s metrosexual man. The method of investigation used the qualitative research literature, making use of articles and books that deal with diverse areas of beauty (philosophy, art history and general fashion, physical education, etc.). Thus, we sought in the historical periods studied, the male beauty and define the characteristics of this, checking the existence of differences and / or similarities in each. It was noticed as well, similarities in each period in relation to beauty as to the forms, use of clothing as a way to strengthen it, symmetry, aesthetic, and exploitation of youth, as to physical similarity between the ancient Egyptians and metrosexual men today. Finally, we observed a male preoccupation with beauty in all periods studied with its own particularities, and this concern is not unique to the female universe.